2000
DOI: 10.1038/sj.onc.1203784
|View full text |Cite
|
Sign up to set email alerts
|

SPAK, a STE20/SPS1-related kinase that activates the p38 pathway

Abstract: We have cloned a member of the STE20/SPS1 protein kinase family from a transformed rat pancreatic beta cell line. SPAK (STE20/SPS1-related, proline alanine-rich kinase) belongs to the SPS1 subfamily of STE20 kinases and is highly conserved between species. SPAK is expressed ubiquitously, although preferentially in brain and pancreas. Biochemical characterization of SPAK catalytic activity demonstrates that is a serine/threonine kinase that can phosphorylate itself and an exogenous substrate in vitro. SPAK is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
138
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(153 citation statements)
references
References 35 publications
14
138
0
Order By: Relevance
“…SPAK, originally termed Ste20/SPS1-related proline-and alaninerich kinase 23 is under the control of AR in LNCaP. 24 Our own data confirm this observation.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S supporting
confidence: 67%
See 2 more Smart Citations
“…SPAK, originally termed Ste20/SPS1-related proline-and alaninerich kinase 23 is under the control of AR in LNCaP. 24 Our own data confirm this observation.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S supporting
confidence: 67%
“…Expression of one kinase, SPAK, 23 increased in androgen-treated LNCaP, and SPAK expression was completely abrogated by the antiandrogen bicalutamide. 24 In addition, SPAK has been described as a kinase that activates the p38 MAP kinase pathway.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…6 The kinase MST1 may act upstream of p38α and c-Jun N-terminal kinase (JNK) in response to oxidative stress. 27,28 In this study, we clearly demonstrated that c-Abl directly phosphorylates p38α and plays a critical role in the MPTP-induced pathogenesis of PD. However, the role of MST1 in c-Abl-mediated p38α activation requires further investigation.…”
Section: Discussionmentioning
confidence: 51%
“…STRAD, a 48-kDa protein, is a pseudokinase that consists of a STE20-like kinase domain but lacks several residues that are indespensible for catalytic activity. STRAD resembles most closely the STE20 homologues SPAK (Johnston et al, 2000) and ILPIP (Sanna et al, 2002), or PAP kinase (Nishigaki et al, 2003). Whereas SPAK is a true kinase, it was later shown that ILPIP/PAPK is a pseudokinase, similarly to STRAD and that it also interacts with and activates LKB1.…”
Section: Introductionmentioning
confidence: 99%